Buyang Huanwu Decoction improves energy metabolism disorders after cerebral ischemia–reperfusion by regulating the SIRT1/AMPK signaling pathway to promote glycolysis and the tricarboxylic acid cycle - Zhongji Hu; Nujiao Deng; Yanling Li; Yang Bai; Xiao Lan; Tingting Xiong; Huang Ding; Xiaodan Liu; Changqing Deng (Chinese Medicine)
Abstract Background Buyang Huanwu Decoction (BYHWD), a traditional Chinese medicine formula for cerebral infarction, exerts neuroprotective effects by enhancing cerebral energy metabolism, yet its precise mechanisms remain elusive. Objective To explore the effects of BYHWD on improving cerebral ischemia–reperfusion injury (CIRI) with Qi deficiency and blood stasis syndrome from an energy metabolism perspective and verify it through experiments. Methods A rat model of CIRI with Qi deficiency and blood stasis syndrome was established and intervened with BYHWD. The therapeutic effect of BYHWD was evaluated using Longa score, Qi deficiency and blood stasis syndrome score, pathological staining, and colorimetric assays. Untargeted metabolomics was used to identify differential metabolites and regulatory mechanisms, and in vivo and in vitro models were constructed for validation. Results BYHWD ameliorated neurological deficits and Qi deficiency and blood stasis syndrome in rats, reduced brain pathology, and increased energy substances. Untargeted metabolomics analysis suggested BYHWD enhanced cerebral energy metabolism via nicotinate and nicotinamide metabolism and AMPK signaling, involving SIRT1/AMPK regulation and promotion of glycolysis and the tricarboxylic acid (TCA) cycle. Validation experiments showed BYHWD activated the SIRT1/AMPK signaling pathway in brain tissue, promoting glucose uptake and enhancing the expression of proteins related to glycolysis, mitochondrial biogenesis, and the TCA cycle. Similar results were observed in HT22 cells subjected to oxygen–glucose deprivation/reperfusion (OGD/R). Conclusion BYHWD improved cerebral energy metabolic disorders by activating the SIRT1/AMPK signaling pathway, thereby enhancing glycolytic capacity and TCA cycle capacity. This study elucidated the mechanisms of BYHWD and provided a theoretical basis for its rational application.